Innovation as a Driving Force for Quality, Efficiency, and Sustainability in Health Services: Innovation in Health Service Quality and Efficiency - Abdul Thalib (CV. Paperhome Indonesia, 2026)
Innovation is no longer optional in health services it is essential. In the face of rising costs, workforce shortages, digital transformation, and increasing public expectations, healthcare systems must move beyond traditional models. Innovation represents a strategic effort to improve quality, enhance efficiency, and ensure long-term sustainability. Achieving high-quality care today requires balancing patient-centered outcomes with responsible resource management. Innovation integrates these goals by redesigning systems, strengthening leadership and collaboration, and leveraging digital and data-driven solutions. From telehealth to community-based prevention, innovation reshapes service delivery to improve resilience and accountability. Sustainable progress demands that innovation be evidence-based, ethical, and equity-oriented. The future of health services depends not on incremental adjustments, but on responsible and strategic innovation that secures lasting impact.